Penggunaan Sempoa Untuk Meningkatkan Keterampilan Berhitung Dengan Media Puzzle - Nur Hidayat; Suhanda Suhanda; Dadi Hamdani; Iif Taufiq El Haque; Pipit Dwi Yuliana; Delia Agustina; Ilma Nurbadiriyah; Satria Dewantara; Wina Wahyuningsih (Yayasan Inspirasi El Burhani, 2023)
Introduction: Counting is a part of mathematics that has an important role in early childhood cognitive development. in learning to count many students feel bored as a result it will interfere with concentration. In minimizing the saturation, counting can be done by using media or tools such as an abacus. Objective: The purpose of this service was To improve basic arithmetic skills in the form of addition, withdrawal, addition and division in grades II and III elementary school students using an abacus media packed with puzzles. Method: This public service was conducted by 5 students, who served as facilitators with the dedication method using education or health counseling about the use of the abacus in improving students' numeracy skills using puzzle media. the target of this counseling is grade II and grade III elementary school students. The counseling activity begins with the pre-test, then the provision of material, after that a post-test is given which ends with an evaluation and a question and answer session. Result: The result of this service is that students are able to operate the beads on the abacus, students are able to understand the concept of reading single or tens of beads on the abacus, students are able to solve advanced story questions and divide using the abacus. Conclusion: The conclusion from the implementation of this community service is counseling about the use of the abacus in improving students' numeracy skills using puzzle media, having a positive effect on students. This was shown by the enthusiasm and activeness of the participants in participating in counseling